Viral infections and molecular mimicry in type 1 diabetes - Coppieters, Ken T.; Wiberg, Anna; von Herrath, Matthias G. (APMIS : acta pathologica, microbiologica et immunologica Scandinavica, 2012)
Type 1 diabetes (T1D) is a disease characterized by inflammation of pancreatic islets associated with autoimmunity against insulin‐producing beta cells, leading to their progressive destruction. The condition constitutes a significant and worldwide problem to human health, particularly because of its rapid, but thus far unexplained, increase in incidence. Environmental factors such as viral infections are thought to account for this trend. While there is no lack of reports associating viral infections toT1D, it has proven difficult to establish which immunological processes link viral infections to disease onset or progression. One of the commonly discussed pathways is molecular mimicry, a mechanism that encompasses cross‐reactive immunity against epitopes shared between viruses and beta cells. In this review, we will take a closer look at mechanistic evidence for a potential role of viruses in T1D, with a special focus on molecular mimicry.